Does the physiological trade-off between reproduction and defense affect the physiological and biochemical parameters of tomato plants infested with Bemisia tabaci MED and MEAM1? - de Lima Toledo, Claudia Aparecida [UNESP]; Oliveira, Moisés Daniel [UNESP]; da Silva Ponce, Franciely [UNESP]; Aires, Eduardo Santana [UNESP]; Seabra Júnior, Santino; Lima, Giuseppina Pace Pereira [UNESP]; de Oliveira, Regiane Cristina [UNESP] (Springer Nature, 2022)
Bemisia tabaci (Gennadius, 1889) (Hemiptera: Aleyrodidae) is one of the main phytosanitary problems found in tomato crops (Solanum lycopersicum L.) in Brazil, causing direct and indirect damage and consequently, physiological and biochemical damage to host plants. This study’s objective was to evaluate the influence of B. tabaci MED and MEAM1 infestation on the physiological and biochemical properties of tomato during the flowering stage. Plants infested with B. tabaci MED and MEAM1 and non-infested plants (control) were studied. Gas exchange, chlorophyll fluorescence, and biochemical parameters (superoxide dismutase (SOD), peroxidase (POD), polyphenol oxidase (PPO), and total phenols) were analyzed. Stomatal conductance (Gs), internal CO2 concentration in leaves (Ci), and transpiration (E) in B. tabaci MED-infested tomato plants were 45 and 38%, 10 and 33%, and 42 and 33% lower than in the control and B. tabaci MEAM1-infested plants, respectively. However, the water use efficiency (WUE) in B. tabaci MED- and MEAM1-infested plants was 38 and 12% higher than in control plants. Plants infested with B. tabaci MEAM1 showed reduced POD activity in the development stages, 3rd and 4th instars, when compared to plants infested with B. tabaci MED by 41 and 50%, respectively. B. tabaci MED-infested plants had lower enzymatic activity (SOD, POD, and PPO) and total phenols at oviposition compared with B. tabaci MEAM1-infested plants. B. tabaci MED infestation during the flowering stage caused alterations in the physiological parameters of tomato plants, while B. tabaci MEAM1 infestation showed less activity of the POD enzyme at all insect pest development stages. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Enzymes; Flowering; Insect–plant relationship; Solanum lycopersicum L; Total phenols